Green innovation-green growth nexus in BRICS: Does financial globalization matter? - Rui Chen; Muhammad Ramzan; Muhammad Hafeez; Sana Ullah (Journal of Innovation & Knowledge (JIK), 2023)
Green growth is a novel theme, gaining prominence in the current era. Therefore, this study investigates the impact of green innovation and financial globalisation on green growth in the BRICS (Brazil, Russia, India, China and South Africa) economies. The study employs the CS-ARDL model for the analysis. The findings confirm that the long-run estimates of environmental innovations and patents are positively significant, ensuring that environment-related technologies are helpful in attaining green growth in the BRICS economies. Moreover, the estimates of financial globalisation are significantly positive, suggesting that a rise in financial globalisation leads to an increase in green growth in the BRICS economies. Our findings imply that, to promote green growth in the BRICS economies, policymakers should focus on R&D activities that can encourage the development of green innovations.
Keywords: 650; BRICS; Financial globalization; Green growth; Green innovation